2020
DOI: 10.1177/0264619620946068
|View full text |Cite
|
Sign up to set email alerts
|

Independent walking and balance in children with CHARGE syndrome

Abstract: Children with CHARGE syndrome (CWCS) are born with multiple physical disabilities, several of which impair balance and the onset of motor milestones. Early motor development problems can include delayed independent walking, which has been found in CWCS. In addition, few studies have examined balance in CWCS and these studies have been limited in scope, necessitating a more comprehensive examination of balance in this population. Motor development occurs as a progression of stages as represented by Seefeldt’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The locomotor skills of the hop and skip are two of the most difficult gross motor skills and require the need for sufficient balance to produce these motor movements. Haibach and Lieberman (2013) and Haibach-Beach et al (2020) have found that children with CHARGE syndrome have limited balance ability, which can directly affect performance on locomotor skills. Furthermore, balance was reported by parents of children with CHARGE syndrome as a rate limiter impeding their child's ability to develop independent walking (Foster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The locomotor skills of the hop and skip are two of the most difficult gross motor skills and require the need for sufficient balance to produce these motor movements. Haibach and Lieberman (2013) and Haibach-Beach et al (2020) have found that children with CHARGE syndrome have limited balance ability, which can directly affect performance on locomotor skills. Furthermore, balance was reported by parents of children with CHARGE syndrome as a rate limiter impeding their child's ability to develop independent walking (Foster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even when these children return from their medical leave, they are often excused from physical education for extended periods of time (Hilgenbrinck et al, 2020). These long absences from physical education and movement opportunities, which would typically improve their gross motor skill performance, may add to existing challenges with balance (Butterfield & Ersing, 1988;Haibach and Lieberman, 2013;Haibach-Beach et al, 2020;Perreault et al, 2020) and vestibular function (Möller, 2011) if they are not provided adapted and individualized services. These balance and vestibular challenges exacerbate the impact of the multiple surgeries and prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that due to the delayed gross motor development of children with CHARGE syndrome, there was a particularly small sample size of participants who were able to independently walk. Children with CHARGE syndrome typically walk independently 30 months later than their peers without disabilities [22]. As such, future research should also examine broader age groups in families with children with severe disabilities.…”
Section: Limitationsmentioning
confidence: 99%
“…Children with CHARGE syndrome walk an average of 25 months later than their sighted peers [19,20]. One reason for this late onset for independent walking is that children with CHARGE syndrome experience more balance issues compared to their peers without disabilities [21,22]. This delayed walking can have drastic impacts on other gross motor skills, such as locomotor and object control skills [23,24], which are critical for engaging in many physical activities.…”
Section: Introductionmentioning
confidence: 99%